THE ROLE OF TRUST ON DIRECT SELLING OF ORIFLAME’S MULTI LEVEL MARKETING - Madjegu, Mahdalena S.; Kindangen, Paulus .; Tielung, Maria V.J (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: Multi level marketing business is rapidly growing especially in North Sulawesi, the one of advantages of multi level marketing business is the contribution it makes to economic growth, one of the examples of multi level marketing in Manado is oriflame’s company. The objective can be achieved of this research is to know the consumer’s trust on the salesperson in a direct selling context as measured by different measures of trust. Theories supporting research are consumer trust and direct selling. This research is qualitative research that uses an exploratory approach with in-depth interviews. The sample of this research is 10 of the consumer oriflame in Manado. The result of this research is in the cognitive trust of the consumer oriflame is they trust to the salesperson and never commitment to build relationship if the goods not really same with the percentage of the salesperson, most of them are never get the stuff that not same with their expectation, so they trust of confidence. For the affective trust, the consumer respect and gratitude to the salesperson and the last is generalized trust the result is they never get conflict with the salesperson so the salesperson could be dependable. Keywords: consumer trust, direct selling, multi level marketing.